Assessment of the quality of life of elderly assisted in a hospital of the Eastern Amazon in the context of the pandemic of COVID-19 (Research, Society and Development, 2023)
Aging causes functional impairment and the occurrence of diseases, which, associated with the COVID-19 pandemic, can impact the quality of life of the elderly. This study aimed to analyze the quality of life of elderly assisted in a geriatric clinic during the COVID-19 pandemic. This is an observational, quantitative, descriptive, cross-sectional epidemiological study. The sample consisted of 35 elderly people attended at the geriatrics clinic for a period of one year, through sociodemographic assessment and the WHOQOL-OLD and WHOQOL-BREF questionnaires, subjected to comparative tests, such as Tukey’s post hoc and the pairwise method comparisons post hoc. The female sex prevailed (77,1%), between 70 and 79 years old (54,3%), mixed (54,2%), with five or more children (74,2%), almost a third of illiterates (31,4%) and a minority of sexually active (17,1%). The men showed a better quality of life in comparison with the women. In the WHOQOL-BREF, the highest average was in the social relationships domain and the lowest in the physical domain. In the WHOQOL-OLD, the intimacy and the past, presente, and future activities facets got the highest average, while the sensory abilities got the lowest average. The physical domain and the past, presente, and future activities facet were related to higher schooling, while the intimacy facet was associated to the marital status married/stable union. The results reflect the profile of patients assisted in the period and the evaluation of the questionnaires showed the importance of social relationships and future perspectives on quality of life. Finally, the pandemic did not have a significant impact on the quality of life of these elderly people.